Quantitative Method for Assessing Crack Retention in Two-Domain Soils: Implications for Agriculture and Infrastructure Stability - Milan Gomboš; Andrej Tall; Branislav Kandra; Dana Pavelková (Geography, Earth Science and Environment: Research Highlights Vol. 8, 2025)
In heavy soils, a high content of clay minerals can cause volume changes as soil moisture fluctuates. Clays and clay minerals are permanent components of the natural environment. Their presence in the soil leads to volume changes, which are three-dimensional processes. These changes result in the formation of cracks in the horizontal plane and vertical movements of the soil surface. The formation of cracks creates a dynamic two-domain structure within the soil, significantly influencing the precipitation-runoff process. However, directly measuring the volume of the crack network is extremely challenging. This study proposes a method for calculating the retention properties of the crack network. The approach is based on the hypothesis that crack volume depends on the clay particle content and soil water content. From a material perspective, the soil profile is classified based on its potential for volume changes. The calculation assesses the isotropy of the soil profile using a geometric factor and incorporates shrinkage characteristics, crack dimensions on the soil surface, and volumetric moisture distribution along the soil profile. To verify the proposed calculation method, temporal changes in crack width and their response to variations in soil bulk moisture were measured and analyzed. As part of the research, a simple tool was developed to accurately measure crack width on the soil surface. The study was conducted in the East Slovak Lowland, where a selected soil profile was examined under extreme drought conditions at the turn of July and August 2022. Crack widths ranged between 1.0 cm and 3.3 cm. The statistical evaluation of the calculation method confirmed its reliability for estimating changes in crack width on the soil surface.